Dampak Ketidakhadiran Ayah terhadap Perkembangan Kepribadian dan Kesejahteraan Emosional Anak: Tinjauan Literatur Sistematis: The Impact of Fatherlessness on Child Personality Development and Emotional Well-being: A Systematic Literature Review - Anugra , Ahmad; Wibowo, Dwi Endrasto; Hamid, Arbain Fajar A. (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2025)
The phenomenon of paternal absence (fatherlessness) has become a serious global issue, particularly in Indonesia, which ranks third worldwide in fatherlessness rates. This research aims to examine comprehensively how the absence of a father figure, whether physical or psychological, affects children's personality development and emotional well-being. The methodology employed is a systematic literature review (SLR) with PRISMA analysis, examining 200 articles from Google Scholar published within the last five years in the Indonesian language. Following the screening process, 8 articles met the inclusion and exclusion criteria for analysis. The research findings demonstrate that paternal absence has significant impacts on children's personality and emotional development, including difficulties in emotion regulation, establishing healthy social relationships, low self-confidence, and increased risk of experiencing anxiety, depression, and aggressive behavior. Boys experiencing fatherlessness tend to exhibit aggressive and rebellious behavior, while girls are more vulnerable to confidence issues and emotional dependence. Conversely, active paternal involvement in child-rearing is proven to enhance social competence, emotional control, academic achievement, and overall personality stability in children. This research is expected to contribute to the development of family psychology knowledge and serve as a foundation for social intervention strategies and more effective family policies in supporting child welfare.